1996
DOI: 10.1515/zna-1996-1-212
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diffusion in the Ionic Plastic Phase of (CH3 )3 NHClO4 Studied by 1H NMR and Electrical Conductivity

Abstract: Spin-lattice relaxation times (7^) and spin-spin relaxation times (T 2 ) of 'H NMR and the electrical conductivity (er) of trimethylammonium Perchlorate were measured in the ionic plastic phase obtainable above 480 K. In this phase, both the cation and anion were revealed to perform selfdiffusion. The activation energy (£ a ) of the cationic diffusion was evaluated to be 55 ±4 and 50 + 4kJmol _1 from 7j and 'H 7 2 respectively, while E a of the anionic diffusion was 64 ±3 kJ mol" 1 from the electrical conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…6 In the case of ionic materials, the diffusion of ionic moieties can lead to sizeable ionic conductivities in the solid-state. 7,8 For inorganic plastic crystals, such as Li 2 SO 4 or a-Na 3 PO 4 , [9][10][11][12] ionic conductivity has been linked in detail to a ''paddle wheel'' type mechanism, where the alkali metal cation diffuses as a direct result of anion rotations. For these salts, however, the plastic phases only occur at temperatures above 600 K. In previous work, we have shown that high conductivities can also be measured in ionic organic salts based on alkyl substituted pyrrolidinium salts with (CF 3 SO 2 ) 2 N 2 , PF 6 2 and BF 4…”
Section: Introductionmentioning
confidence: 99%
“…6 In the case of ionic materials, the diffusion of ionic moieties can lead to sizeable ionic conductivities in the solid-state. 7,8 For inorganic plastic crystals, such as Li 2 SO 4 or a-Na 3 PO 4 , [9][10][11][12] ionic conductivity has been linked in detail to a ''paddle wheel'' type mechanism, where the alkali metal cation diffuses as a direct result of anion rotations. For these salts, however, the plastic phases only occur at temperatures above 600 K. In previous work, we have shown that high conductivities can also be measured in ionic organic salts based on alkyl substituted pyrrolidinium salts with (CF 3 SO 2 ) 2 N 2 , PF 6 2 and BF 4…”
Section: Introductionmentioning
confidence: 99%
“…Trimethylammonium perchlorate is known to have three solid phases above room temperature (Stammler et al, 1966). These solid phases have been characterized in a wide temperature range of 90-530 K by 1 H NMR (Jurga, 1984;Ishida & Furukawa, 1996), 35 Cl NMR (Jurga et al, 1986), Raman and IR (Mylrajan & Srinivasan, 1988), powder and single-crystal Xray diffraction (Ishida et al, 1994), as well as by electrical conductivity (Ishida & Furukawa, 1996). The high-temperature cubic phase is stable above 480 K and is an ionic plastic phase (Ikeda, 2004), in which both cation and anion perform isotropic rotation as well as self-diffusion.…”
Section: Commentmentioning
confidence: 99%
“…In the 1980s and 1990s, OIPCs based on ammonium salts were reported by mainly Japanese researchers. [19][20][21][22][23][24][25][26] Recently, new OIPCs with pyrrolidinium, [27][28][29][30] imidazolium, 31,32 phosphonium, 33,34 and metallocenium [35][36][37] cations have been discovered and vigorously studied. Regarding anions, not only common anions of interest such as BF 4 À and PF 6 À but also B(CN) 4 À , 38 FeCl 4 À , 38 B(CH 2 CH 3 ) 3 (CH 3 ) À , 39 perfluorobutane sulfonate, 40 and various other anion species have been reported.…”
Section: Introductionmentioning
confidence: 99%